PENGELOLAAN SEKOLAH TERPADU - Pratiwi, Asih; Wahyudi, Wahyudi; Aswandi, Aswandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractIntegrated education is basically organizing education that includes elementary, junior high, high school in 1 integrated management. The integration in question is that it can be physically or managementally.This study aims to obtain information about the management of one-roof schools in improving the quality of education in each school managed by Al-Mumtaz Pontianak, including planning, organizing, directing and supervising.. Selected informants are informants who can provide information needed in research. Checking the validity of the findings is done by member checking and triangulation. Analysis of the data used is the analysis of the description of the Miles Huberman model.The results of the study can be concluded as follows: (1) school management in integrated planning has been implemented well in making the vision, mission, goals and programs of the school has been going well (2) school management in integrated organizing is appropriate where in making and running the program in accordance with the capabilities of employees (3) management in integrated speech has been carried out in formulating goals, analyzing the potential of the school, providing motivation and appreciation to educators, and trying to create a conducive school environment (4) management in integrated supervision is where it has been implemented well .Keywords: Management, One-Stop School